Digital Transformation Through Local E-Catalogs in Improving Micro, Small and Medium Enterprises in Badung Regency - Putu Eka Purnamaningsih; Kadek Wiwin Dwi Wismayanti (International Journal of Educational Research Excellence (IJERE), 2023)
Digital transformation is a change in activities or activities from conventional to digital through the use of technology. The existence of digital transformation has an influence on various sectors, one of which is the Micro, Small and Medium Enterprises sector. Micro, Small and Medium Enterprises are productive businesses owned by individuals or business entities that are in accordance with standards as micro enterprises. The purpose of this research is to find out how the development of e-government through local e-catalog in increasing Micro, Small and Medium Enterprises in Badung Regency. This research uses qualitative research with descriptive methods. Data collection techniques by observation, interviews, questionnaires, literature studies and documentation. The results of this study show 3 elements of successful implementation of E-government in the Badung Regency Government Procurement Section, namely: 1. Support elements, namely the support and willingness of the Head of the Badung Regency Government Procurement Section and support through regulations ( laws). 2. Capacity elements, which include the availability of supporting resources such as financial resources, the existence of adequate infrastructure resources such as computers, internet, and printers as well as the availability of competent human resources. 3. Value element, which is related to the benefits felt by the government and society.